Oracle 11g for dummies - Zeis, Chris (Wiley, 2009)
Are you a seasoned system administrator charged with setting up an Oracle database? Or did you suddenly become a DBA by default? If database administration with Oracle is part of your job, you'll be glad to have Oracle 11g For Dummies in your.
Print version record
Keywords: Oracle (Computer file); Database management; Relational databases; Bases de données; Gestion; Bases de données relationnelles; COMPUTERS; Data Processing